Dependence of construction industry on foreign labour in Malaysia / Mohd Nazeri Mohammad - Mohammad, Mohd Nazeri (2006)
Manpower is one of the most pressing challenges facing the construction industry, as there is heavily reliance on a large number of foreign workers. The Economic Report 2001/ 2002; states that the construction sector employed 769,300 workers, 70 % of which are foreigners. Productivity is generally slow as employment is of short duration, seasonal and there is little training on the many skilled involves. The construction industry is a vehicle through which a nation's physical developments are activated by initiating projects from blueprint stage to implementation and materialisation that can bring about benefits to the people and the nation, thus contributing to national growth and in uplifting the status of the nation's economy. The ability of the construction industry to remain competitive lies in the strength of its fundamental elements, namely manpower, material supply, plant and equipment, finance, technology, and management. Of paramount of its development of human resources in which both the public and private sector has importance roles to play. The government policy announced in January 2002 to limit Indonesian foreign workers for employment to the plantation and domestic help sectors and the amendments to Immigration Act 2002 which took effect on August 1, 2002 result in abrupt disruption of labour supply to the construction industry, which ultimately affects product quality and efficiency of the delivery system.